2018
DOI: 10.1007/s11482-018-9640-1
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Medical and Personality Correlates of Psychological Well-Being among People Living with HIV: a Latent Profile Analysis

Abstract: The aim of this study was to examine the heterogeneity of the sample of people living with HIV (PLWH) in terms of psychological well-being (PWB) using the latent profile analysis. Participants were 530 people with confirmed diagnosis of HIV+. The study was cross-sectional with psychological well-being operationalized by health related quality of life (WHO Quality of Life-BREF), satisfaction with life (Satisfaction with Life Scale) and positive and negative general affect (PANAS-X). The Big Five personality tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
(56 reference statements)
3
4
1
Order By: Relevance
“…Emotionally reactive individuals demonstrated levels of optimism and extraversion that were similar to individuals with high SWB. Similar results were obtained in studies using a person-centered approach to examine the structure of well-being among individuals with diagnoses of HIV (Rzeszutek et al, 2019) and among self-employed (Bujacz et al, 2020). Rzeszutek et al (2019) applied a latent profile analysis (LPA) to seven well-being indicators (somatic health, psychological health, social relationships, environment, positive affect, negative affect, and life satisfaction) and found six distinct classes: medium, low, high, mixed, very low, and very high well-being.…”
Section: Results Of Previous Research Using a Personcentered Approach To Well-beingsupporting
confidence: 81%
See 2 more Smart Citations
“…Emotionally reactive individuals demonstrated levels of optimism and extraversion that were similar to individuals with high SWB. Similar results were obtained in studies using a person-centered approach to examine the structure of well-being among individuals with diagnoses of HIV (Rzeszutek et al, 2019) and among self-employed (Bujacz et al, 2020). Rzeszutek et al (2019) applied a latent profile analysis (LPA) to seven well-being indicators (somatic health, psychological health, social relationships, environment, positive affect, negative affect, and life satisfaction) and found six distinct classes: medium, low, high, mixed, very low, and very high well-being.…”
Section: Results Of Previous Research Using a Personcentered Approach To Well-beingsupporting
confidence: 81%
“…The detection of profiles with patterns different from congruous does not support a variable-centered approach, which posits that individuals differ only in mean levels of life satisfaction, positive affect, and negative affect, assuming there is population homogeneity (low or high SWB) in the configuration of SWB components (Busseri et al, 2009). However, the identification of both congruous and incongruous SWB profiles is in line with the assumptions of the dynamic and modular model of SWB (Shmotkin, 2005), as well as with the results of previous studies using a person-centered approach (Bergman & Daukantaite, 2009;Busseri et al, 2009;Rzeszutek et al, 2019). Incongruous profiles similar to a mixed SWB and moderately low SWB were detected in at least two studies conducted on non-clinical samples (Busseri et al, 2009;Bergman & Daukantaite, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, several recent studies have shown that psychosocial variables outweighed the medical parameters as predictors and correlates of psychological well-being (PWB) of PLWH (e.g. Cooper, Clatworthy, Harding, Whetham, & Consortium, 2017 ; Rzeszutek, Gruszczyńska, & Firląg-Burkacka, 2018 ). However, PLWH still suffer from intense HIV-related distress and consistently report a much poorer well-being level when compared to patients suffering from other chronic illnesses (Cooper et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Well-being is also proposed in six components which are purpose in life, environmental mastery, positive relationships, personal growth, autonomy and self-acceptance [ 12 ]. Although factors that affect the well-being may vary according to cultural influences, personality or social background [ 8 , 13 ], the six core values remain the same. Well-being is not a stable state.…”
Section: Introductionmentioning
confidence: 99%